Attachment styles and marital satisfaction among selected couples in Meycauayan City - Decilio, Maria Sheryl O.
This study used a descriptive correlational type of research design to determine the factors that influence marital satisfaction among 50 married couples in Meycauayan City, who are 30 to 50 years old with civil and/or church marriage for 10 to 20 years, living together in one house and have one or more children. Respondents were selected using systematic random sampling. Results showed that husbands and wives who have secure attachment style have higher degree of marital satisfaction compared to those with dismissing, preoccupied, and fearful-avoidant attachment. Wives were found to be more educated, more securely attached, and have higher degree of marital satisfaction than their husbands while husbands were more fearful-avoidant that their wives. Dismissing attachment had the greatest negative impact on husbands' marital satisfaction which may make husbands greatly decrease their physical attraction and sexual satisfaction towards their wives. Husbands not having a good overall family life when still single had higher secure attachment. This may be due to their effort in having a better family life at present. Married couple's religion, type of residence, and family background influenced marital satisfaction. In contrast, age, years of marriage, monthly income, and number of children did not influence marital satisfaction. Trusting the spouse and give and take relationship are ways married couples can do strengthen their marital relationship. Further research on marital satisfaction among spouses who differ in attachment style with their own spouses may also be studied.